The Legal Qualification of Liability in the Field of Cosmetic Surgery - BENMESSAOUD, Chahrazed (Journal of Human Sciences, 2025)
Cosmetic surgery has held significant importance in human life since ancient times, as it aims to introduce improvements to the human body. With the increasing demand for cosmetic procedures, there has been a corresponding rise in medical errors.it raises substantial legal issues, due to its unique nature and the legislative shortcomings in addressing this type of medical error and defining the nature of liability. This often leads the patient, as a victim of such medical error, to seek appropriate compensation for the serious harm suffered. However, the patient is confronted with the difficulty of proving the error of the. Consequently, jurisprudence and the judiciary, in order to provide greater protection and assurance for the patient, have inclined towards establishing the principles of objective liability as an alternative to fault-based liability for compensating medical errors in the field of cosmetic surgery, thereby ensuring both civil and criminal liability.